Microbial and Haemagglutinins from the Serum of Estuarine Crab Portunus sanguinolentus - A. Amsath3, S. Vincent2, B. Meena1, Sumith rose1, S.S. Jayaraj2 (Recent Research in Science and Technology, 2011)
A naturally occurring haemagglutinin (HA), with activity against bacteria and yeast cells were detected in the serum of Portunus sanguinolentus using mammalian erythrocytes (RBC), various bacteria and yeast as indicator cells. The serum gave highest HA titer with buffalo RBC, tripsinized yeast, Vibrio fluvialis and Vibrio alginolyticus. An analysis of the biological properties of the HA showed it to be specifically dependent on the presence of Ca2+ for its activity. Further studies demonstrated that the HA- inhibition assays performed with carbohydrates revealed that the serum HA was specific for non-reducing terminal glucose with 1-2 glucosidic linkages. Thus this agglutinin appears to be unique among all the known crustacean agglutinins.